FOUR USM PRESS PUBLISHED JOURNALS LISTED IN EMERGING SOURCES CITATION INDEX, ESCI THOMSON REUTERS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 28 September 2015 Four journals published by Universiti Sains Malaysia Press (USM Press) have been listed in the Thomson Reuters soon to be launched database named the Web of Science (WoS) Emerging Sources Citation Index (ESCI).